Lycopene counteracts the hepatic response to 7,12-dimethylbenz[a]anthracene by altering the expression of Bax, Bcl-2, caspases, and oxidative stress biomarkers - Agca, Can Ali; Tuzcu, Mehmet; Gencoglu, Hasan; Akdemir, Fatih; Ali, Shakir; Şahin, Kazım; Küçük, Ömer (Taylor & Francis Ltd, 2012)
Context: Lycopene is a carotenoid found in tomato, watermelon, pink grapefruit, and guava in high concentration. Dietary intake of lycopene has been proposed to inversely correlate with the risk of cancer. It has also been reported to provide protection against cellular damage caused by reactive oxygen species, which makes it worthwhile to study the effect of lycopene on liver damage in rat model. Objective: In this study, we report the effect of lycopene on 7,12-dimethylbenz[a]-anthracene (DMBA)-induced expression of Bax, Bcl-2, caspases, and oxidative stres biomarkers in the liver. Materials and methods: Lycopene was administered orally at 20 mg/kg body weight for 20 weeks followed by the intraperitoneal injection of DMBA (50 mg/kg body weight) on day 1 and day 30 of the experiment. Control rats received vehicle (olive oil) or DMBA alone. Rats were sacrificed after completion of the treatment. Results: We observed that the levels of Bax, caspase-3, and caspase-9 decreased to 44, 67, and 43%, respectively, and Bcl-2 increased by 80% in DMBA-treated rats. Lycopene reversed the changes in the respective groups, and decreased the level of Bcl-2 to 25%, while increasing the Bax to 42% when compared to DMBA control. Lycopene increased the expression of caspase-3 (82.09%) and caspase-9 (58.96%), and attenuated the level of hepatic malondialdehyde (41%) and 8-isoprostane (40%) when compared to the respective controls. Glutathione (GSH) decreased significantly in DMBA group (15.89%), but reached the normal level in lycopene-treated animals. Hepatic lycopene concentration in treated rats was 8.2 nmol/g tissue. Conclusion: The study reports that lycopene counteracts the hepatic response to DMBA by altering the expression of Bax, Bcl-2, caspases, and oxidative stress biomarkers in animal model.
Keywords: Animal models; cancer prevention; apoptosis; liver